Teaching about graffiti and street art to undergraduate students at u.s. universities: Confronting challenges and seizing opportunities - Ross, Jeffrey; Lennon, John (Journal of Interdisciplinary Studies in Education, 2018)
This paper reviews two scholars’ experiences teaching about the subjects of graffiti and street art to undergraduate students in U.S. universities. Using auto-ethnographical methods, the instructors review the challenges that they encountered and the various strategies they experimented with to overcome these difficulties. Issues discussed include the unique composition of the student body, the methods by which the students were introduced to the subject matter, choice of readings, assignments, and evaluation procedures. The authors progress from a slow and perhaps cautious introduction of the material on graffiti and street art into existing classes, to a full-fledged course on the subject matter. Suggestions are presented for other instructors considering teaching a class or assignments on the subject matter of graffiti and street art.